2015
DOI: 10.1007/s00113-015-0061-4
|View full text |Cite
|
Sign up to set email alerts
|

Augmentationstechnik am proximalen Humerus

Abstract: The augmentation of the screws in locked plating in a proximal humerus fracture model is effective in improving the primary stability in a cyclic varus bending test. The targeted augmentation of two particular screws in a region of low bone quality within the humeral head was almost as effective as four screws with twice the amount of bone cement. Screw augmentation combined with a knowledge of the local bone quality could be more effective in enhancing the primary stability of a proximal humerus locking plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…If the surgeon is not able to achieve anatomic reduction and restoration of the MCS intraoperatively, then as many as possible of the medial support screws should be placed to restore the medial mechanical stability. In addition, other strategies for structural augmentation in the locking plate fixation of PHFs include intramedullary fibular grafts,[ 22 23 24 ] calcium phosphate or sulfate cement,[ 25 26 ] and iliac crest bone autologous grafting. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…If the surgeon is not able to achieve anatomic reduction and restoration of the MCS intraoperatively, then as many as possible of the medial support screws should be placed to restore the medial mechanical stability. In addition, other strategies for structural augmentation in the locking plate fixation of PHFs include intramedullary fibular grafts,[ 22 23 24 ] calcium phosphate or sulfate cement,[ 25 26 ] and iliac crest bone autologous grafting. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…Their studies made use of the same fracture model involving the proximal humerus (AO 11B1), with a separated greater tuberosity and a 1-cm fracture gap below the anatomical neck. 9,13,22 Lesser angles of displacement reduce the tendency to varization of fixations in osteoporotic bone, as observed in clinical routine. 12,25 Unger and his research team also found a negative correlation between bone density and number of cycles to implant failure in their non-augmented group, leading to the view that low bone density reduces the longevity of osteosyntheses so that augmentation could be considered a good treatment option, especially in osteoporotic bone.…”
Section: Discussionmentioning
confidence: 84%
“…The fracture model was a three-part fragment fracture at the proximal humerus with a 10-mm gap below the anatomical neck and a greater tuberosity osteotomy (AO type 11B1, see Figure 1); this fracture model has already been used by several research groups. 9,13,22 Fracture fixation was achieved with the well-established fixation tool, the Targon Ò PH (Aesculap AG, Tuttlingen, Germany; length: 160 mm; diameter proximal: 10 mm, distal: 8 mm). Stabilization in all specimens involved the insertion of three head screws and two bicortical shaft screws.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the use of calcar screws as well as of polyaxial ones which ameliorate the stable fixation thanks to inserting the latter into the dorso-medial part of the humeral head [ 15 ], the biomechanical stability of the plate osteosynthesis can, furthermore, be significantly increased by cement augmentation of the screws [ 15 , 29 , 30 ] or by using bone grafts (i.e., fibular grafts, femoral head, iliac crest chips) [ 31 ].…”
Section: Introduction: Proximal Humerus Fracturementioning
confidence: 99%